Radiation cooling ceramic glaze and radiation cooling building ceramic tile and preparation method thereof
Patent Information
- Application Number
- CN202611520591.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-29
- Publication Date
- 2026-10-30
AI Technical Summary
专利CN 121362029A通过在陶瓷砖坯体表面制备连通微孔结构的硅酸二钙(C2S)基功能釉层,然后利用硅酸二钙的高碳化反应活性,通过原位碳化反应,使釉层转变形成为以纳米或微米级碳酸钙晶粒为主要组分、镶嵌了纳米硫酸钡晶粒的牢固表层,提升了陶瓷砖的太阳光反射比和大气透明窗口发射率,实现了陶瓷砖的辐射制冷功能;但是,碳化产物(CaCO3)力学性能较差,以及微孔结构也会使得釉层硬度降低;而且制备工艺复杂,分段煅烧工艺与建筑陶瓷的工业制造工况匹配性较低,而且原位碳化处理耗时较长,难以规模化推广应用
(1)本发明是通过陶瓷釉层中各结晶相之间以及结晶相与非晶相之间的界面结构实现对太阳光的高效散射,与传统的利用气孔Mie散射提升太阳光反射比的机制不同,本发明更易制得致密的高硬度陶瓷釉层,从而可确保辐射制冷建筑陶瓷砖的加工、运输与服役安全性与可靠性,可有效避免辐射制冷陶瓷砖在加工、运输与服役过程中发生釉层破损与污染,继而有利于延长辐射制冷陶瓷砖的使用寿命。
Smart Images

Figure CN123003146A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional building ceramics technology, specifically relating to a radiation-cooled ceramic glaze and a radiation-cooled building ceramic brick and their preparation method. Background Technology
[0002] Radiation cooling, a passive cooling method based on the spontaneous cooling of objects due to spectral characteristic responses, achieves cooling by radiating infrared energy from the object's surface into outer space. It is an emerging zero-energy cooling technology. In recent years, significant progress has been made in the research of radiation-cooled materials, covering various types such as organic materials, inorganic materials, and organic-inorganic composite materials. Among them, radiation-cooled building ceramics outperform traditional polymer-based or metal film materials in terms of optical performance, durability, and environmental friendliness, while also demonstrating significant application value in building energy conservation, safety protection, and carbon emission reduction.
[0003] The key to the development and application of radiation-cooling ceramic materials lies in optimizing the photothermal properties of the materials, namely, improving the solar reflectance (0.3~2.5 μm, including ultraviolet, visible and near-infrared bands) and the atmospheric transparency window emissivity (8~13 μm). By radiating heat into the universe through the atmospheric transparency window, zero-energy radiation cooling can be achieved. At the same time, the high solar reflectance reduces the heat input to the ceramic surface, thereby enhancing the cooling effect and enabling the ceramic to perform daytime radiation cooling. Patent CN 121362029A describes a method for preparing a dicalcium silicate (C2S)-based functional glaze layer with interconnected microporous structures on the surface of ceramic tile blanks. Utilizing the high carbonization reactivity of dicalcium silicate, an in-situ carbonization reaction transforms the glaze layer into a robust surface layer primarily composed of nano- or micro-sized calcium carbonate grains embedded with nano-barium sulfate grains. This enhances the solar reflectance and atmospheric transparency window emissivity of the ceramic tile, achieving a radiative cooling function. However, the carbonization products (CaCO3) exhibit poor mechanical properties, and the microporous structure reduces the glaze layer's hardness. Furthermore, the preparation process is complex, the segmented calcination process is poorly compatible with the industrial manufacturing conditions of building ceramics, and the in-situ carbonization process is time-consuming, hindering large-scale application. Patent CN 119591321A, while utilizing a composite of nanoporous alumina and metal oxide-doped magnesium aluminum spinel to improve the solar reflectance of building ceramics, lacks performance data on atmospheric transparency window emissivity, making it difficult to assess its radiative cooling function. Patents CN 122145198A and CN 122102516A both use trivalent europium ions (Eu). 3+ Doping with magnesium aluminum spinel powder enhances the emissivity of ceramic glazes. On one hand, europium is a rare earth element, scarce, difficult to extract, and expensive; on the other hand, Eu... 3+ Its ionic radius (0.0947 nm) is much larger than that of the Al it is theoretically meant to replace. 3+The significant difference (0.0535nm) can easily lead to lattice distortion, making the doping and substitution process more difficult; thus limiting the large-scale application of this type of technology. Patent CN 117756409A utilizes diatomaceous earth-loaded mesoporous alumina and SiC high-temperature foaming to introduce a porous structure in the glaze layer, improving the solar reflectivity of ceramic tiles. However, the porous structure easily leads to a decrease in the stain resistance and surface hardness of ceramic tiles. Chi Yan Tso et al. (Hierarchically structured passive radiative cooling ceramic with high solar reflectivity, Science, 2023, 382: 691–697; CN 117534506 A) developed hierarchical porous alumina ceramics using a phase transition method. The porous structure improves light scattering and the solar reflectivity of the ceramic, giving it excellent radiative cooling function. However, its preparation process is complex and difficult to directly apply to the large-scale manufacturing of building ceramics. Moreover, the porous structure leads to a decrease in the hardness and stain resistance of the ceramic. In addition, the porous structure easily leads to the adsorption of dust and atmospheric pollutants, which in turn changes the surface structure of ceramics and reduces the solar reflectance and atmospheric transparency window emissivity of ceramics. Moreover, the porous structure reduces the hardness of the ceramic glaze, making ceramic tiles prone to glaze wear and damage during processing and transportation, and also deteriorating their radiative cooling function. Summary of the Invention
[0004] In view of this, the present invention improves the solar reflectance of ceramic glaze by controlling the phase composition of ceramic glaze and utilizing the refractive index differences between crystalline phases and between crystalline and amorphous phases. By introducing Si-O, Al-O, Zr-O, and Zn-O chemical bonds through chemical composition design, the present invention achieves a higher mid-infrared emissivity of ceramic glaze, thereby realizing the radiative cooling function of building ceramic tiles. At the same time, based on the crystalline phase composition design, the surface hardness of ceramic glaze is effectively improved, which can ensure the highly reliable application of radiative cooling building ceramics.
[0005] In a first aspect, the present invention provides a radiation-cooled ceramic glaze. The chemical composition of the radiation-cooled ceramic glaze comprises, by mass percentage: SiO2 16%~25%; Al2O3 15%~36%; ZnO 5%~21%; ZrO2 23%~37%; Fe2O3 0.1%~0.3%; TiO2 0%~0.1%; CaO 0.3%~1.5%; MgO 0.1%~0.2%; K2O 1.5%~2.3%; Na2O 2.2%~3.7%; BaO 0.1%~0.7%; B2O3 3%~6%; Y2O3 0.8%~2%; and loss on ignition 1%~2%.
[0006] In an optional embodiment, the mineral composition of the radiation-cooled ceramic glaze includes: 5-15 parts potassium feldspar, 5-10 parts kaolin, 5-20 parts calcined zinc oxide, 3-15 parts calcium-zinc frit, 0-15 parts zirconium silicate, 15-35 parts yttrium-stabilized zirconium oxide, 10-20 parts high-boron frit, and 10-30 parts alumina, based on a total mineral composition of 100 parts by mass.
[0007] In an optional embodiment, the chemical composition of the calcium-zinc frit includes, by mass percentage: SiO2 50%~60%; Al2O3 10%~15%; ZnO 6%~11%; ZrO2 0~0.5%; Fe2O3 0~0.1%; TiO2 0~0.1%; CaO 8%~10%; MgO 1%~1.5%; K2O 3%~6%; Na2O 1%~3%; BaO 3%~5%; loss on ignition 0~1%; the chemical composition of the high-boron frit includes, by mass percentage: SiO2 32%~40%; Al2O3 5%~15%; Fe2O3 0~0.3%; TiO2 0~0.1%; CaO 0~0.2%; MgO 0~0.2%; K2O 4%~6%; Na2O 12%~20%; B2O3 25%~35%; loss on ignition 0.5%~1.5%.
[0008] In an optional embodiment, the phase composition of the radiation-cooled ceramic glaze after firing is mainly crystalline phase, with t-ZrO2, m-ZrO2, ZrSiO4, ZnAl2O4, and Al2O3 being the main crystalline phases.
[0009] Secondly, the present invention provides a radiation-cooled building ceramic tile. The radiation-cooled building ceramic tile comprises a radiation-cooled ceramic glaze layer formed using the aforementioned radiation-cooled ceramic glaze.
[0010] In an optional embodiment, the solar reflectance of the radiation-cooled ceramic brick is ≥93%, and the emissivity of the atmospheric transparency window is ≥90%.
[0011] Thirdly, the present invention provides a method for preparing radiant cooling building ceramic bricks, comprising the following steps: Step 1: Apply a surface glaze to the ceramic body and allow it to dry. Step 2: Apply the radiation-cooled ceramic glaze to the surface of the ceramic blank obtained in step 1 and dry it again; Step 3: The ceramic blank obtained in step 2 is fired to produce radiation-cooled building ceramic bricks.
[0012] In an optional embodiment, the radiation-cooled ceramic glaze is applied by glazing; the specific gravity of the radiation-cooled ceramic glaze is 1.80~1.95 g / cm³.3 The glaze application rate is 1200~2000 g / m². 2 .
[0013] In an optional embodiment, the chemical composition of the surface glaze includes, by mass percentage: SiO2 50%~58%; Al2O3 25%~30%; Fe2O3 0.2%~0.5%; TiO2 0~0.2%; CaO 0.5%~1%; MgO 0.1%~0.5%; K2O 2%~5%; Na2O 2%~3.5%; ZrO2 4%~8%; and loss on ignition 3%~6%.
[0014] In an optional embodiment, the glaze is applied by pouring or spraying; the specific gravity of the glaze is 1.40~1.55 g / cm³. 3 The glaze application rate is 450~650 g / m². 2 .
[0015] In an optional embodiment, the firing temperature is 1120~1160 ℃ and the firing time is 30~60 min.
[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention achieves efficient scattering of sunlight through the interface structure between the crystalline phases and between the crystalline and amorphous phases in the ceramic glaze. Unlike the traditional mechanism of using pores and Mie scattering to improve the reflectance of sunlight, this invention is more likely to produce a dense and high-hardness ceramic glaze, thereby ensuring the safety and reliability of the processing, transportation and service of radiative cooling building ceramic bricks. It can effectively avoid glaze damage and contamination during the processing, transportation and service of radiative cooling ceramic bricks, and thus help extend the service life of radiative cooling ceramic bricks.
[0017] (2) The crystalline phases (t-ZrO2, m-ZrO2, ZrSiO4, ZnAl2O4, Al2O3) of the radiation-cooled ceramic glaze prepared by the present invention not only have high hardness, but also have excellent mid-infrared emission performance, so that the radiation-cooled ceramic brick has both high hardness and high atmospheric transparency window emissivity. Attached Figure Description
[0018] Figure 1 The solar reflectance spectrum and mid-infrared emission spectrum of the radiation-cooled building ceramic bricks prepared in Example 1; Figure 2 The XRD pattern of the glaze layer on the surface of the radiation-cooled ceramic brick prepared in Example 1; Figure 3 The solar reflectance spectrum and mid-infrared emission spectrum of the radiation-cooled building ceramic bricks prepared in Example 2; Figure 4To obtain the solar reflectance spectrum and mid-infrared emission spectrum of the radiation-cooled building ceramic tile for Comparative Example 2; Figure 5 XRD patterns of ordinary building ceramic white bricks were prepared for Comparative Example 2. Detailed Implementation
[0019] The present invention is further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention.
[0020] Currently, radiation-cooled ceramic glazes are typically porous. For example, CN 121362029A describes a microporous structure of calcium carbonate and barium sulfate; CN 119591321A, CN 122145198A, CN 122102516A, and CN 117756409A all utilize porous alumina powder; and CN 117534506A yields radiation-cooled ceramics with a porosity as high as 70%. While porous structures are beneficial for achieving efficient scattering of the solar spectrum and improving the solar reflectance of ceramics, they also tend to reduce the stain resistance, surface hardness, and wear resistance of radiation-cooled ceramics, thus limiting their large-scale application in building ceramics. Therefore, this invention develops a radiation-cooled ceramic glaze, building ceramic bricks prepared using it, and a preparation method thereof. The main improvements compared to existing technologies include: (1) This invention regulates the phase composition of ceramic glaze through chemical composition design. By utilizing the refractive index differences between crystalline phases and between crystalline and amorphous phases, the scattering efficiency of the ceramic glaze to the solar spectrum is improved, thereby increasing the solar reflectance of the ceramic glaze. Furthermore, by using chemical composition design to regulate the phase composition, Si-O, Al-O, Zr-O, Zn-O, and Si-O-Al chemical bonds (characteristic absorption peaks located in the mid-infrared band) can be introduced, which is beneficial to achieving a higher atmospheric transparency window emissivity of the ceramic glaze, thereby realizing the radiative cooling function of building ceramic tiles.
[0021] (2) Through the formulation design of ceramic glaze, this invention achieves the efficient introduction of ZrO2, ZrSiO4, ZnAl2O4 and Al2O3 crystalline phases. At the same time, calcium-zinc frit and high-boron frit are used to achieve the sintering densification of ceramic glaze layer. The surface hardness of building ceramic bricks is effectively improved by using crystalline phase enhancement and densification enhancement, which can lay an excellent structural foundation for the realization of the radiation cooling function of building ceramic bricks.
[0022] In an embodiment of the present invention, the chemical composition of the radiation-cooled ceramic glaze of the present invention includes, by mass percentage: SiO2 16%~25%; Al2O3 15%~36%; ZnO 5%~21%; ZrO2 23%~37%; Fe2O3 0.1%~0.3%; TiO2 0%~0.1%; CaO 0.3%~1.5%; MgO 0.1%~0.2%; K2O 1.5%~2.3%; Na2O 2.2%~3.7%; BaO 0.1%~0.7%; B2O3 3%~6%; Y2O3 0.8%~2%; and loss on ignition 1%~2%.
[0023] It should be understood that any mineral composition that causes the chemical composition of the radiation-cooled ceramic glaze to fall within the above-mentioned range is applicable to the present invention. In an optional embodiment, the mineral composition of the radiation-cooled ceramic glaze includes: 5-15 parts potassium feldspar, 5-10 parts kaolin, 5-20 parts calcined zinc oxide, 3-15 parts calcium-zinc frit, 0-15 parts zirconium silicate, 15-35 parts yttrium-stabilized zirconium oxide, 10-20 parts high-boron frit, and 10-30 parts alumina, based on 100 parts by mass of the total mineral composition.
[0024] In an optional embodiment, the yttrium-stabilized zirconium oxide in the mineral raw material of the radiation-cooled ceramic glaze is 3YSZ (3 mol% Y₂O₃ stabilized ZrO₂) powder, with a phase composition of t-ZrO₂. The chemical composition of the yttrium-stabilized zirconium oxide may include: by mass percentage, 4.5%~5.5% Y₂O₃ and 94.5%~95.5% ZrO₂. For example, the median particle size (D) of the yttrium-stabilized zirconium oxide powder... 50 The median particle size of yttrium oxide-stabilized zirconia powder is 1~3 μm. If the median particle size of the submicron-sized powder is too small, the hard agglomeration of the submicron-sized powder will easily lead to a decrease in the stability of the radiation-cooled ceramic slurry; if the median particle size of the yttrium oxide-stabilized zirconia powder is too large, it will reduce the Mie scattering efficiency of the residual t-ZrO2 crystalline phase in the glaze layer, which is not conducive to improving the solar reflectance of radiation-cooled ceramic tiles.
[0025] In the mineral raw materials of the radiation-cooled ceramic glaze, the alumina powder has a purity of ≥99.5% and a median particle size (D). 50 The median particle size of alumina is 1~5 μm. If the median particle size of alumina is too small, the hard agglomeration of submicron-sized particles can easily lead to a decrease in the stability of the radiation-cooled ceramic slurry. If the median particle size of alumina is too large, on the one hand, it will reduce the Mie scattering efficiency of the residual alumina crystal phase in the glaze layer, which is not conducive to improving the solar reflectance of radiation-cooled ceramic tiles; on the other hand, it will inhibit the melting of alumina powder raw materials in the high-temperature glass phase, reduce the reactivity of Al2O3 and ZnO, which is not conducive to the precipitation of ZnAl2O4 crystal phase, and is not conducive to improving the atmospheric transparency window emissivity and surface Vickers hardness of ceramic tiles.
[0026] It is worth noting that the zirconium silicate in the radiation-cooled ceramic glaze is artificially synthesized ZrSiO4, and its radionuclide limits should meet the following requirements: internal exposure index ≤ 7 and external exposure index ≤ 5. Due to the presence of naturally occurring radioactive elements such as U and Th in natural zirconium silicate (zircon), the radionuclide limits of the resulting building ceramic products are prone to exceeding the requirements for Class A decorative and finishing materials in GB 6566 (internal exposure index ≤ 1.0, external exposure index ≤ 1.3). Therefore, this invention uses artificially synthesized ZrSiO4, which, because it does not rely on natural ores containing impurities, allows for controllable radionuclide limits, with an internal exposure index ≤ 7 and an external exposure index ≤ 5. This ensures that the radionuclide limits of the radiation-cooled ceramic glaze fully meet the requirements for Class A decorative and finishing materials in GB 6566.
[0027] The mineral raw materials of the radiation-cooled ceramic glaze, specifically the calcium-zinc frit, have the following chemical composition by mass percentage: SiO2 50%~60%; Al2O3 10%~15%; ZnO 6%~11%; ZrO2 0~0.5%; Fe2O3 0~0.1%; TiO2 0~0.1%; CaO 8%~10%; MgO 1%~1.5%; K2O 3%~6%; Na2O 1%~3%; BaO 3%~5%; and a loss on ignition of 0~1%. It should be understood that any mineral composition that results in the chemical composition of the calcium-zinc frit falling within the above range is applicable to this invention. The calcium-zinc frit used in the embodiments of this invention was obtained through commercial purchase.
[0028] The high-boron frit in the mineral raw materials of the radiation-cooled ceramic glaze comprises, by mass percentage: SiO2 32%~40%; Al2O3 5%~15%; Fe2O3 0~0.3%; TiO2 0~0.1%; CaO 0~0.2%; MgO 0~0.2%; K2O 4%~6%; Na2O 12%~20%; B2O3 25%~35%; and loss on ignition 0.5%~1.5%. It should be understood that any mineral composition that results in the chemical composition of the high-boron frit falling within the above range is applicable to this invention. The high-boron frit used in the embodiments of this invention was obtained through commercial purchase.
[0029] The following describes the preparation method of radiant cooling building ceramic tiles. The preparation method includes the following steps: Step 1: Apply a surface glaze to the ceramic body and then dry it. Step 2: Apply radiation-cooled ceramic glaze to the surface of the ceramic blank obtained in Step 1 and perform drying treatment; Step 3: The ceramic blank obtained in step 2 is fired to produce radiation-cooled building ceramic bricks.
[0030] It is worth noting that the ceramic green body is a conventional green body in the field of building ceramics, and this invention does not limit the chemical composition of the ceramic green body. As an example, but not limited to, the chemical composition of the green body includes, by mass percentage: SiO2 65%~70%; Al2O3 18%~20%; Fe2O3 0.5%~1.3%; TiO2 0~0.3%; CaO 0.5%~3%; MgO 0.5%~3%; K2O 2%~4%; Na2O 1%~2%; loss on ignition 3%~5%. The ceramic green body is then dried.
[0031] A surface glaze is applied to the dried ceramic surface. The surface glaze is a conventional glaze used in the production of architectural ceramic tiles, and this invention does not limit the chemical composition of the surface glaze. The main functions of the surface glaze include covering the body, improving the whiteness of the body, and providing an exhaust channel during the high-temperature firing process, thus preventing defects in the ceramic glaze surface caused by radiation cooling. As an example, but not limited to, the chemical composition of the surface glaze includes, by mass percentage: SiO2 50%~58%; Al2O3 25%~30%; Fe2O3 0.2%~0.5%; TiO2 0~0.2%; CaO 0.5%~1%; MgO 0.1%~0.5%; K2O 2%~5%; Na2O 2%~3.5%; ZrO2 4%~8%; and loss on ignition 3%~6%. The surface glazes used in the various embodiments and comparative examples were obtained through commercial purchase.
[0032] Prepare the surface glaze slurry. Weigh the raw materials containing the surface glaze mineral composition according to the surface glaze mineral composition. Mill the surface glaze mineral composition, additives, and water evenly, and sieve to obtain the surface glaze slurry. Additives may include sodium carboxymethyl cellulose and / or sodium tripolyphosphate. The mass ratio of sodium carboxymethyl cellulose to the surface glaze mineral composition can be 0.1%~0.5%. The mass ratio of sodium tripolyphosphate to the surface glaze mineral composition can be 0.1%~0.5%. Before applying the surface glaze, water can be added to the surface glaze slurry to adjust to the desired surface glaze specific gravity.
[0033] The glaze is applied by pouring or spraying. Preferably, the specific gravity of the glaze is 1.40~1.55 g / cm³. 3 The glaze application rate is 450~650 g / m². 2 .
[0034] Prepare a radiation-cooled ceramic glaze slurry. Mix the radiation-cooled ceramic glaze mineral composition with additives and water until homogeneous, then sieve to obtain the radiation-cooled ceramic glaze slurry. Mixing methods include, but are not limited to, ball milling. In an optional embodiment, the additive is a diluent (a conventional process in the field of building ceramics preparation). The diluent is, for example, any one of water glass, sodium humate, sodium polyacrylate, or sodium tripolyphosphate, at a dosage of 0.5% to 1.0% (by mass fraction) of the radiation-cooled ceramic glaze mineral composition. Since kaolin acts as a suspending agent in the sodium tripolyphosphate formulation, sodium carboxymethyl cellulose can be added to the radiation-cooled ceramic glaze slurry, or not. Use a ball milling process, for example, to control the slurry sieve residue to 0.3 wt% to 0.5 wt% (passing through 325 mesh). Water can be added to the radiation-cooled ceramic glaze slurry before applying the radiation-cooled ceramic glaze to adjust to the desired specific gravity.
[0035] The radiation-cooled ceramic glaze can be applied by pouring. The specific gravity of the radiation-cooled ceramic glaze is 1.80~1.95 g / cm³. 3 The glaze application rate is 1200~2000 g / m². 2 If the amount of glaze applied to the radiative cooling ceramic is too low, the glaze layer will be too thin, which will reduce its solar reflectivity. On the other hand, if the amount of glaze applied is too high and the glaze layer is too thick, although it will not have much impact on the solar reflectivity and atmospheric transparency window emissivity of the radiative cooling ceramic, it will have an adverse effect on the shape of the radiative cooling ceramic tile and increase its manufacturing cost.
[0036] It is worth noting that the application of radiation-cooled ceramic glaze can be achieved not only by pouring glaze, but also by spraying glaze and dry application, all of which fall within the scope of this invention. This invention does not limit the method of applying the radiation-cooled ceramic glaze, as long as the process can meet the required amount of glaze to be applied.
[0037] It is worth noting that drying is a conventional production process for building ceramics, and this invention does not impose any special limitations on it. For example, warm air drying is a standard operation in the production of building ceramic bricks. In an optional embodiment, the drying temperature is 150~250 ℃, and the drying time is 5~10 min.
[0038] The firing temperature of the radiation-cooled ceramic bricks is 1120~1160 ℃, and the firing time is 30~60 min. The phase composition of the fired radiation-cooled ceramic glaze is mainly crystalline phase, with t-ZrO2, m-ZrO2, ZrSiO4, ZnAl2O4, and Al2O3 being the main crystalline phases.
[0039] Radiation-cooled ceramic tiles have a solar reflectance of ≥93% and an atmospheric transparency window emissivity of ≥90%.
[0040] The main optimization mechanism / principle of photothermal performance (solar reflectance, atmospheric transparency window emissivity) involved in this invention is as follows: The radiation-cooled ceramic bricks prepared by this invention mainly utilize the formulation and chemical composition design of the glaze layer (radiation-cooled ceramic glaze) to achieve the control of its phase composition. On the one hand, it can improve the solar reflectance (0.3~2.5 μm) and atmospheric transparency window emissivity (8~13 μm) of the ceramic bricks, thereby optimizing the radiation-cooling function of the ceramic bricks. On the other hand, by utilizing the crystalline phase enhancement and densification of the glaze layer, it can ensure that the radiation-cooled ceramic bricks have high surface hardness.
[0041] This invention regulates the phase composition of ceramic glazes through glaze formulation and chemical composition design. The phase composition of the radiation-cooled ceramic glaze is dominated by crystalline phases, specifically t-ZrO2 (m-ZrO2), ZrSiO4, ZnAl2O4, and Al2O3. The refractive indices of t-ZrO2, ZrSiO4, ZnAl2O4, and Al2O3, and the silicate glass phase, are 2.0~2.2, 1.9~2.0, 1.8, 1.7~1.8, and 1.5~1.6, respectively. Therefore, the refractive index differences between the crystalline phases and between the crystalline and amorphous phases can be utilized to improve the scattering efficiency of sunlight by the ceramic glaze, thereby increasing its solar reflectance. Furthermore, while regulating the phase composition of the ceramic glaze through chemical composition design, Si-O, Al-O, Zr-O, Zn-O, and Si-O-Al chemical bonds can be introduced, with characteristic absorption peaks located at 400~1300 cm⁻¹, respectively. -1 400~760 cm -1 400~800 cm -1 400~680 cm -1 1030~1080 cm -1 It is basically in the mid-infrared band (700~1200 cm). -1 This facilitates the achievement of a high atmospheric transparency window emissivity in ceramic glazes, thereby enabling the radiative cooling function of building ceramic tiles.
[0042] This invention improves the crystalline phase content of radiative cooling ceramic glazes through ceramic glaze formulation design (the XRD pattern shows virtually no visible amorphous phase "bun" peaks, indicating that the ceramic glaze's phase composition is dominated by crystalline phases). It also achieves the efficient introduction of ZrO2, ZrSiO4, ZnAl2O4, and Al2O3 crystalline phases. The Vickers hardness of ZrO2, ZnAl2O4, and Al2O3 reaches 10-16 GPa, and that of ZrSiO4 reaches 8-12 GPa, both higher than the Vickers hardness of silicate glass (5-7 GPa). Simultaneously, the use of calcium-zinc frit and high-boron frit achieves sintering densification of the ceramic glaze layer. This crystalline phase reinforcement and densification enhance the surface hardness of the building ceramic tiles, laying an excellent structural foundation for realizing the radiative cooling function of building ceramic tiles.
[0043] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values in the examples below.
[0044] Example 1 A method for preparing a radiation-cooled building ceramic brick mainly includes the following steps: Step 1: Prepare ceramic green bodies by dry pressing of ceramic green body powder, and then dry them (hot air drying temperature: 150 ℃, drying time: 5 min). The chemical composition of the ceramic green body includes, by mass percentage: SiO2 68.1%; Al2O3 18.4%; Fe2O3 1.2%; TiO2 0.2%; CaO 2.1%; MgO 1.0%; K2O 2.8%; Na2O 1.5%; loss on ignition 4.7%.
[0045] Step 2: Then, apply a surface glaze to the surface of the blank obtained in Step 1 using a spray glazing method, followed by drying (hot air drying temperature 150 ℃, drying time 5 min). The chemical composition of the surface glaze includes, by mass percentage: SiO2 53.5%; Al2O3 27.5%; Fe2O3 0.3%; CaO 0.9%; MgO 0.3%; K2O 3.8%; Na2O 2.6%; ZrO2 6.3%; loss on ignition 4.8%. The specific gravity of the surface glaze is controlled at 1.40 g / cm³. 3 Glazing amount is 650 g / m 2 .
[0046] Step 3: Weigh out 15 parts by mass of potassium feldspar, 5 parts by mass of kaolin, 5 parts by mass of calcined zinc oxide, 5 parts by mass of calcium-zinc frit (its chemical composition is: by mass percentage, SiO2 55.6%; Al2O3 12.4%; ZnO 8.3%; ZrO2 0.1%; Fe2O3 0.1%; CaO 9.7%; MgO 1.2%; K2O 5.0%; Na2O 2.4%; BaO 4.6%; loss on ignition 0.6%), 15 parts by mass of zirconium silicate (artificially synthesized ZrSiO4, internal irradiation index 6.8, external irradiation index 4.5), and 15 parts by mass of yttrium-stabilized zirconium oxide (3YSZ, its chemical composition includes: by mass percentage, Y2O3 5.5%, ZrO2 94.5%; D... 50 10 parts by mass of high boron frit (its chemical composition includes, by mass percentage: SiO2 36.8%; Al2O3 10.0%; Fe2O3 0.3%; TiO2 0.1%; CaO 0.2%; MgO 0.1%; K2O 5.0%; Na2O 16.7%; B2O3 30.0%; loss on ignition 0.8%), and 30 parts by mass of alumina (purity 99.5%, D... 50 A glaze slurry was prepared by ball milling 0.5 parts by weight of water glass, 55 parts by weight of water, and 200 parts by weight of high-alumina grinding balls (5 μm in diameter) in a ball mill jar. The slurry residue was then controlled to be 0.3 wt% (325 mesh) by adjusting the ball milling time, and the specific gravity of the slurry was controlled to be 1.80 g / cm³ by adjusting the water content. 3 Thus, a radiation-cooled ceramic glaze can be prepared for use (its chemical composition includes, by mass percentage: SiO2 24.5%; Al2O3 35.8%; ZnO 5.4%; ZrO2 23.9%; Fe2O3 0.1%; CaO 0.5%; MgO 0.1%; K2O 2.3%; Na2O 2.3%; BaO 0.2%; B2O3 3.0%; Y2O3 0.8%; loss on ignition 1.1%).
[0047] Step 4: Apply a radiation-cooled ceramic glaze to the surface of the ceramic body obtained in Step 2 using a glazing method. The glaze application amount is 2000 g / m². 2 Then, it is dried (hot air drying temperature is 250 ℃, drying time is 10 min).
[0048] Step 5: The ceramic blank obtained in Step 4 is fired in a roller kiln at a temperature of 1160 ℃ for 45 min.
[0049] Step 6: After firing, the edges are ground, film is applied, and the bricks are packaged to obtain the radiation-cooled building ceramic bricks.
[0050] 70 mm × 150 mm ceramic samples were randomly cut using an external circular cutter. The solar reflectance and mid-infrared emission spectra of the radiation-cooled building ceramic tiles were measured using a UV-Vis-NIR spectrophotometer and a Fourier transform infrared spectrometer, respectively, as shown in the attached figure. Figure 1 As shown. According to JG / T 235-2014 and T / CECS 10378-2024, the solar reflectance and atmospheric transparent window emissivity of the radiation-cooled building ceramic tiles are 93% and 90%, respectively. The stain resistance performance of the radiation-cooled ceramic tiles is measured to be level 5 using GB / T 3810.14-2016.
[0051] The XRD pattern of the glaze layer on the surface of radiation-cooled building ceramic tiles was measured using an X-ray diffractometer, as shown in the attached figure. Figure 2 As shown, no obvious amorphous "bun peaks" were observed in its XRD pattern, indicating that the phase composition of the prepared radiation-cooled ceramic glaze is mainly crystalline, and the crystalline phases are mainly t-ZrO2, m-ZrO2, ZrSiO4, ZnAl2O4, and Al2O3 crystalline phases, with only a small amount of SiO2 crystalline phase. On the one hand, the refractive index differences between various crystalline phases and between crystalline and amorphous phases can be utilized to improve the scattering efficiency of ceramic glaze on sunlight, thereby increasing the solar reflectance of ceramic glaze. On the other hand, by utilizing the introduced Si-O, Al-O, Zr-O, Zn-O, and Si-O-Al chemical bonds, a higher atmospheric transparency window emissivity of ceramic glaze can be achieved, thus enabling the radiative cooling function of building ceramic tiles. In addition, the high crystalline phase content is also beneficial to improving the surface hardness of radiative cooling ceramic glaze. The Vickers hardness of radiative cooling ceramic glaze was measured to be 8.6 GPa using Vickers indentation (0.5 kgf loading, held for 15 s). The higher hardness is beneficial to improving the wear resistance of radiative cooling ceramic tiles and ensuring the safety and reliability of processing, transportation, and service of radiative cooling building ceramic tiles, thereby extending the service life of radiative cooling ceramic tiles.
[0052] Example 2
[0053] A method for preparing a radiation-cooled building ceramic brick mainly includes the following steps: Step 1: Prepare ceramic green bodies by dry pressing of ceramic green body powder, and then dry them (hot air drying temperature: 150 ℃, drying time: 5 min). The chemical composition of the ceramic green body includes, by mass percentage: SiO2 68.1%; Al2O3 18.4%; Fe2O3 1.2%; TiO2 0.2%; CaO 2.1%; MgO 1.0%; K2O 2.8%; Na2O 1.5%; loss on ignition 4.7%.
[0054] Step 2: Then, apply a surface glaze to the ceramic body obtained in Step 1 using a spray glazing method, followed by drying (hot air drying temperature 150 ℃, drying time 5 min). The chemical composition of the surface glaze includes, by mass percentage: SiO2 53.5%; Al2O3 27.5%; Fe2O3 0.3%; CaO 0.9%; MgO 0.3%; K2O 3.8%; Na2O 2.6%; ZrO2 6.3%; loss on ignition 4.8%. The specific gravity of the surface glaze is controlled at 1.55 g / cm³. 3 Glazing amount is 450 g / m 2 .
[0055] Step 3: Weigh out 5 parts by mass of potassium feldspar, 5 parts by mass of kaolin, 15 parts by mass of calcined zinc oxide, 10 parts by mass of calcium-zinc frit (its chemical composition includes, by mass percentage: SiO2 55.6%; Al2O3 12.4%; ZnO 8.3%; ZrO2 0.1%; Fe2O3 0.1%; CaO 9.7%; MgO 1.2%; K2O 5.0%; Na2O 2.4%; BaO 4.6%; loss on ignition 0.6%), and 30 parts by mass of yttrium-stabilized zirconium oxide (3YSZ, its chemical composition includes, by mass percentage: Y2O3 5.5%, ZrO2 94.5%; D...). 50 20 parts by mass of high boron frit (its chemical composition includes, by mass percentage: SiO2 36.8%; Al2O3 10.0%; Fe2O3 0.3%; TiO2 0.1%; CaO 0.2%; MgO 0.1%; K2O 5.0%; Na2O 16.7%; B2O3 30.0%; loss on ignition 0.8%) and 15 parts by mass of alumina (purity 99.5%, D... 50 The glaze slurry was prepared by ball milling with 1.0 part by weight of sodium polyacrylate (1 μm), 50 parts by weight of water, and 200 parts by weight of high-alumina grinding balls in a ball mill jar. The slurry residue was then controlled to be 0.3 wt% (325 mesh) by adjusting the ball milling time, and the specific gravity of the glaze slurry was controlled to be 1.95 g / cm³ by adjusting the water content. 3 Thus, a radiation-cooled ceramic glaze can be prepared for use (its chemical composition includes, by mass percentage: SiO2 18.8%; Al2O3 20.8%; ZnO 15.8%; ZrO2 28.4%; Fe2O3 0.1%; CaO 1.0%; MgO 0.2%; K2O 2.1%; Na2O 3.7%; BaO 0.5%; B2O3 6.0%; Y2O3 1.6%; loss on ignition 1.0%).
[0056] Step 4: Apply a radiation-cooled ceramic glaze to the surface of the ceramic body obtained in Step 2 using a glazing method. The glaze application amount is 1200 g / m².2 Then, it is dried (hot air drying temperature is 250 ℃, drying time is 8 min).
[0057] Step 5: The ceramic blank obtained in Step 4 is fired in a roller kiln at a temperature of 1140 ℃ for 60 min.
[0058] Step 6: After firing, the edges are ground, film is applied, and the bricks are packaged to obtain the radiation-cooled building ceramic bricks.
[0059] 70 mm × 150 mm ceramic samples were randomly cut using an external circular cutter. The solar reflectance and mid-infrared emission spectra of the radiation-cooled building ceramic tiles were measured using a UV-Vis-NIR spectrophotometer and a Fourier transform infrared spectrometer, respectively, as shown in the attached figure. Figure 3 As shown. According to JG / T 235-2014 and T / CECS 10378-2024, the solar reflectance and atmospheric transparent window emissivity of the radiation-cooled building ceramic tiles are calculated to be 95% and 91%, respectively. The stain resistance of the radiation-cooled ceramic tiles is measured to be level 5 using GB / T 3810.14-2016. Furthermore, the Vickers hardness of the radiation-cooled ceramic glaze is measured to be 8.1 GPa using Vickers indentation (0.5 kgf loading, held for 15 s).
[0060] Example 3
[0061] A method for preparing a radiation-cooled building ceramic brick mainly includes the following steps: Step 1: Prepare ceramic green bodies by dry pressing of ceramic green body powder, and then dry them (hot air drying temperature: 150 ℃, drying time: 5 min). The chemical composition of the ceramic green body includes, by mass percentage: SiO2 68.1%; Al2O3 18.4%; Fe2O3 1.2%; TiO2 0.2%; CaO 2.1%; MgO 1.0%; K2O 2.8%; Na2O 1.5%; loss on ignition 4.7%.
[0062] Step 2: Then, apply a surface glaze to the ceramic body obtained in Step 1 using a spray glazing method, followed by drying (hot air drying temperature 150 ℃, drying time 5 min). The chemical composition of the surface glaze includes, by mass percentage: SiO2 53.5%; Al2O3 27.5%; Fe2O3 0.3%; CaO 0.9%; MgO 0.3%; K2O 3.8%; Na2O 2.6%; ZrO2 6.3%; loss on ignition 4.8%. The specific gravity of the surface glaze is controlled at 1.50 g / cm³. 3 Glazing amount is 550 g / m 2 .
[0063] Step 3: Weigh out 5 parts by mass of potassium feldspar, 10 parts by mass of kaolin, 20 parts by mass of calcined zinc oxide, 3 parts by mass of calcium-zinc frit (its chemical composition includes, by mass percentage: SiO2 55.6%; Al2O3 12.4%; ZnO 8.3%; ZrO2 0.1%; Fe2O3 0.1%; CaO 9.7%; MgO 1.2%; K2O 5.0%; Na2O 2.4%; BaO 4.6%; loss on ignition 0.6%), 5 parts by mass of zirconium silicate (artificially synthesized ZrSiO4, internal irradiation index 6.8, external irradiation index 4.5), and 35 parts by mass of yttrium-stabilized zirconium oxide (3YSZ, its chemical composition includes, by mass percentage: Y2O3 5.5%, ZrO2 94.5%; D... 50 12 parts by mass of high boron frit (its chemical composition includes, by mass percentage: SiO2 36.8%; Al2O3 10.0%; Fe2O3 0.3%; TiO2 0.1%; CaO 0.2%; MgO 0.1%; K2O 5.0%; Na2O 16.7%; B2O3 30.0%; loss on ignition 0.8%) and 10 parts by mass of alumina (purity 99.5%, D... 50 The glaze slurry was prepared by ball milling with 1.0 part by weight of sodium humate (2 μm), 55 parts by weight of water, and 200 parts by weight of high-alumina grinding balls in a ball mill jar. The slurry residue was then controlled to be 0.3 wt% (325 mesh) by adjusting the ball milling time, and the specific gravity of the glaze slurry was controlled to be 1.90 g / cm³ by adjusting the water content. 3 Thus, a radiation-cooled ceramic glaze can be prepared for use (its chemical composition includes, by mass percentage: SiO2 16.2%; Al2O3 15.9%; ZnO 20.1%; ZrO2 36.3%; Fe2O3 0.2%; CaO 0.3%; MgO 0.1%; K2O 1.5%; Na2O 2.3%; BaO 0.1%; B2O3 3.6%; Y2O3 1.9%; loss on ignition 1.5%).
[0064] Step 4: Apply a radiation-cooled ceramic glaze to the surface of the ceramic body obtained in Step 2 using a glazing method. The glaze application amount is 1500 g / m². 2 Then, it is dried (hot air drying temperature is 200 ℃, drying time is 8 min).
[0065] Step 5: The ceramic blank obtained in Step 4 is fired in a roller kiln at a temperature of 1120 ℃ for 60 min.
[0066] Step 6: After firing, the edges are ground, film is applied, and the bricks are packaged to obtain the radiation-cooled building ceramic bricks.
[0067] 70 mm × 150 mm ceramic samples were randomly cut using an external cylindrical cutter. According to JG / T 235-2014 and T / CECS 10378-2024, the solar reflectance and atmospheric transparent window emissivity of the radiation-cooled building ceramic tiles were measured to be 97% and 91%, respectively. The stain resistance of the radiation-cooled ceramic tiles was determined to be level 5 using GB / T 3810.14-2016. Furthermore, the Vickers hardness of the radiation-cooled ceramic glaze was measured to be 8.8 GPa using Vickers indentation (0.5 kgf loading, held for 15 s).
[0068] Example 4
[0069] A method for preparing a radiation-cooled building ceramic brick mainly includes the following steps: Step 1: Prepare ceramic green bodies by dry pressing of ceramic green body powder, and then dry them (hot air drying temperature: 150 ℃, drying time: 5 min). The chemical composition of the ceramic green body includes, by mass percentage: SiO2 68.1%; Al2O3 18.4%; Fe2O3 1.2%; TiO2 0.2%; CaO 2.1%; MgO 1.0%; K2O 2.8%; Na2O 1.5%; loss on ignition 4.7%.
[0070] Step 2: Then, apply a surface glaze to the ceramic body obtained in Step 1 using a spray glazing method, followed by drying (hot air drying temperature 150 ℃, drying time 5 min). The chemical composition of the surface glaze includes, by mass percentage: SiO2 53.5%; Al2O3 27.5%; Fe2O3 0.3%; CaO 0.9%; MgO 0.3%; K2O 3.8%; Na2O 2.6%; ZrO2 6.3%; loss on ignition 4.8%. The specific gravity of the surface glaze is controlled at 1.50 g / cm³. 3 Glazing amount is 550 g / m 2 .
[0071] Step 3: Weigh out 5 parts by mass of potassium feldspar, 8 parts by mass of kaolin, 10 parts by mass of calcined zinc oxide, 15 parts by mass of calcium-zinc frit (its chemical composition includes, by mass percentage: SiO2 55.6%; Al2O3 12.4%; ZnO 8.3%; ZrO2 0.1%; Fe2O3 0.1%; CaO 9.7%; MgO 1.2%; K2O 5.0%; Na2O 2.4%; BaO 4.6%; loss on ignition 0.6%), 7 parts by mass of zirconium silicate (artificially synthesized ZrSiO4, internal irradiation index 6.8, external irradiation index 4.5), and 20 parts by mass of yttrium-stabilized zirconium oxide (3YSZ, its chemical composition includes, by mass percentage: Y2O3 5.5%, ZrO2 94.5%; D...50 15 parts by mass of high boron frit (its chemical composition includes, by mass percentage: SiO2 36.8%; Al2O3 10.0%; Fe2O3 0.3%; TiO2 0.1%; CaO 0.2%; MgO 0.1%; K2O 5.0%; Na2O 16.7%; B2O3 30.0%; loss on ignition 0.8%) and 20 parts by mass of alumina (purity 99.5%, D... 50 The glaze slurry was prepared by ball milling with 0.8 parts by weight of sodium tripolyphosphate (3 μm), 55 parts by weight of water, and 200 parts by weight of high-alumina grinding balls in a ball mill jar. The slurry residue was then controlled to be 0.3 wt% (325 mesh) by adjusting the ball milling time, and the specific gravity of the glaze slurry was controlled to be 1.85 g / cm³ by adjusting the water content. 3 Thus, a radiation-cooled ceramic glaze can be prepared for use (its chemical composition includes, by mass percentage: SiO2 23.4%; Al2O3 27.0%; ZnO 11.2%; ZrO2 23.5%; Fe2O3 0.2%; CaO 1.5%; MgO 0.2%; K2O 2.2%; Na2O 3.1%; BaO 0.7%; B2O3 4.5%; Y2O3 1.1%; loss on ignition 1.4%).
[0072] Step 4: Apply a radiation-cooled ceramic glaze to the surface of the ceramic body obtained in Step 2 using a glazing method. The glaze application amount is 1600 g / m². 2 Then, it is dried (hot air drying temperature is 200 ℃, drying time is 8 min).
[0073] Step 5: The ceramic blank obtained in Step 4 is fired in a roller kiln at a temperature of 1135 ℃ for 40 min.
[0074] Step 6: After firing, the edges are ground, film is applied, and the bricks are packaged to obtain the radiation-cooled building ceramic bricks.
[0075] 70 mm × 150 mm ceramic samples were randomly cut using an external circular cutter. According to JG / T 235-2014 and T / CECS 10378-2024, the solar reflectance and atmospheric transparent window emissivity of the radiation-cooled building ceramic tiles were measured to be 95% and 93%, respectively. The stain resistance of the radiation-cooled ceramic tiles was determined to be level 5 using GB / T 3810.14-2016. Furthermore, the Vickers hardness of the radiation-cooled ceramic glaze was measured to be 9.1 GPa using Vickers indentation (0.5 kgf loading, held for 15 s).
[0076] Comparative Example 1 A method for preparing a radiation-cooled building ceramic brick mainly includes the following steps: Step 1: Prepare ceramic green bodies by dry pressing of ceramic green body powder, and then dry them (hot air drying temperature: 150 ℃, drying time: 5 min). The chemical composition of the ceramic green body includes, by mass percentage: SiO2 68.1%; Al2O3 18.4%; Fe2O3 1.2%; TiO2 0.2%; CaO 2.1%; MgO 1.0%; K2O 2.8%; Na2O 1.5%; loss on ignition 4.7%.
[0077] Step 2: Then, apply a surface glaze to the ceramic body obtained in Step 1 using a spray glazing method, followed by drying (hot air drying temperature 150 ℃, drying time 5 min). The chemical composition of the surface glaze includes, by mass percentage: SiO2 53.5%; Al2O3 27.5%; Fe2O3 0.3%; CaO 0.9%; MgO 0.3%; K2O 3.8%; Na2O 2.6%; ZrO2 6.3%; loss on ignition 4.8%. The specific gravity of the surface glaze is controlled at 1.40 g / cm³. 3 Glazing amount is 650 g / m 2 .
[0078] Step 3: Weigh out 15 parts by mass of potassium feldspar, 5 parts by mass of kaolin, 5 parts by mass of calcined zinc oxide, 5 parts by mass of calcium-zinc frit (its chemical composition includes, by mass percentage: SiO2 55.6%; Al2O3 12.4%; ZnO 8.3%; ZrO2 0.1%; Fe2O3 0.1%; CaO 9.7%; MgO 1.2%; K2O 5.0%; Na2O 2.4%; BaO 4.6%; loss on ignition 0.6%), 15 parts by mass of zirconium silicate (artificially synthesized ZrSiO4, internal irradiation index 6.8, external irradiation index 4.5), and 15 parts by mass of yttrium-stabilized zirconium oxide (3YSZ, its chemical composition includes, by mass percentage: Y2O3 5.5%, ZrO2 94.5%; D... 50 10 parts by mass of high boron frit (its chemical composition includes, by mass percentage: SiO2 36.8%; Al2O3 10.0%; Fe2O3 0.3%; TiO2 0.1%; CaO 0.2%; MgO 0.1%; K2O 5.0%; Na2O 16.7%; B2O3 30.0%; loss on ignition 0.8%), and 30 parts by mass of alumina (purity 99.5%, D... 50A glaze slurry was prepared by ball milling 0.5 parts by weight of water glass, 55 parts by weight of water, and 200 parts by weight of high-alumina grinding balls (5 μm in diameter) in a ball mill jar. The slurry residue was then controlled to be 0.3 wt% (325 mesh) by adjusting the ball milling time, and the specific gravity of the slurry was controlled to be 1.80 g / cm³ by adjusting the water content. 3 Thus, a radiation-cooled ceramic glaze can be prepared for use (its chemical composition includes, by mass percentage: SiO2 24.5%; Al2O3 35.8%; ZnO 5.4%; ZrO2 23.9%; Fe2O3 0.1%; CaO 0.5%; MgO 0.1%; K2O 2.3%; Na2O 2.3%; BaO 0.2%; B2O3 3.0%; Y2O3 0.8%; loss on ignition 1.1%).
[0079] Step 4: Apply a radiation-cooled ceramic glaze to the surface of the ceramic body obtained in Step 2 using a glazing method. The glaze application amount is 1000 g / m². 2 Then, it is dried (hot air drying temperature is 250 ℃, drying time is 10 min).
[0080] Step 5: The ceramic blank obtained in Step 4 is fired in a roller kiln at a temperature of 1160 ℃ for 45 min.
[0081] Step 6: After firing, the edges are ground, film is applied, and the bricks are packaged to obtain the radiation-cooled building ceramic bricks.
[0082] 70 mm × 150 mm ceramic samples were randomly cut using an external circular cutter. According to JG / T 235-2014 and T / CECS 10378-2024, the solar reflectance and atmospheric transparent window emissivity of the radiation-cooled building ceramic tile were calculated to be 86% and 90%, respectively. The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the specific gravity of the radiation-cooled ceramic glaze was 1.80 and the glaze application amount was 1000 g / m³. 2 In Example 1, the specific gravity of the radiation-cooled ceramic glaze was 1.80, and the glaze application rate was 2000 g / m³. 2 All other preparation process parameters were the same. Due to the reduced application amount of the radiation-cooled ceramic glaze, the solar reflectance of the obtained radiation-cooled ceramic brick was reduced, by 7% compared to the radiation-cooled building ceramic brick obtained in Example 1, which was detrimental to improving the radiation-cooling performance of the building ceramic brick.
[0083] Comparative Example 2 A method for preparing ordinary building ceramic white bricks mainly includes the following steps: Step 1: Prepare ceramic green bodies by dry pressing of ceramic green body powder, and then dry them (hot air drying temperature: 150 ℃, drying time: 5 min). The chemical composition of the ceramic green body includes, by mass percentage: SiO2 68.1%; Al2O3 18.4%; Fe2O3 1.2%; TiO2 0.2%; CaO 2.1%; MgO 1.0%; K2O 2.8%; Na2O 1.5%; loss on ignition 4.7%.
[0084] Step 2: Then, apply a surface glaze to the ceramic body obtained in Step 1 using a spray glazing method, followed by drying (hot air drying temperature 150 ℃, drying time 5 min). The chemical composition of the surface glaze includes, by mass percentage: SiO2 53.5%; Al2O3 27.5%; Fe2O3 0.3%; CaO 0.9%; MgO 0.3%; K2O 3.8%; Na2O 2.6%; ZrO2 6.3%; loss on ignition 4.8%. The specific gravity of the surface glaze is controlled at 1.40 g / cm³. 3 Glazing amount is 650 g / m 2 .
[0085] Step 3: Apply a protective glaze to the surface of the ceramic body obtained in Step 2 using a spray glazing method. The protective glaze is a transparent glaze commonly used in the production of architectural ceramics, and its chemical composition includes, by mass percentage: SiO2 53.4%; Al2O3 11.5%; Fe2O3 0.1%; CaO 8.3%; MgO 3.4%; K2O 0.3%; Na2O 5.2%; BaO 2.0%; SrO 1.7%; ZnO 2.9%; and loss on ignition 11.2%. The specific gravity of the protective glaze slurry is 1.60 g / cm³. 3 Glazing amount is 750 g / m 2 Then, it is dried (hot air drying temperature is 250 ℃, drying time is 5 min).
[0086] Step 4: The ceramic blank obtained in Step 3 is fired in a roller kiln at a temperature of 1140 ℃ for 35 min.
[0087] Step 5: After firing, the edges are ground, film is applied, and the bricks are packaged to produce ordinary building ceramic white bricks.
[0088] 70 mm × 150 mm ceramic samples were randomly cut using an external cylindrical cutter. The solar reflectance and mid-infrared emission spectra of ordinary white building ceramic bricks were measured using a UV-Vis-NIR spectrophotometer and a Fourier transform infrared spectrometer, respectively, as shown in the attached figures. Figure 4As shown. According to JG / T 235-2014 and T / CECS 10378-2024, the solar reflectance and atmospheric transparent window emissivity of ordinary building ceramic white bricks are 60% and 87%, respectively, which are much lower than those of the radiation-cooled building ceramic bricks prepared in Example 1.
[0089] In addition, the XRD pattern of the glaze layer on the surface of ordinary white ceramic building bricks was measured using an X-ray diffractometer, as shown in the attached figure. Figure 5 As shown, the XRD pattern reveals distinct amorphous "bun peaks," indicating that the phase composition of the prepared ordinary building ceramic white brick glaze layer is mainly amorphous, containing only small amounts of SiO2 (quartz) and KAlSi3O8 (microcline) crystalline phases. Furthermore, the Vickers hardness of the ordinary building ceramic white brick glaze layer, measured using Vickers indentation (0.5 kgf loading, held for 15 s), is only 5.3 GPa, significantly lower than that of the radiation-cooled building ceramic glaze layer prepared in Example 1. This demonstrates that the technical solution proposed in this invention can not only produce radiation-cooled building ceramic bricks with high solar reflectance and high atmospheric transparency window emissivity, but also high-hardness ceramic bricks.
[0090] Comparative Example 3 A method for preparing a radiation-cooled building ceramic brick mainly includes the following steps: Step 1: Prepare ceramic green bodies by dry pressing of ceramic green body powder, and then dry them (hot air drying temperature: 150 ℃, drying time: 5 min). The chemical composition of the ceramic green body includes, by mass percentage: SiO2 68.1%; Al2O3 18.4%; Fe2O3 1.2%; TiO2 0.2%; CaO 2.1%; MgO 1.0%; K2O 2.8%; Na2O 1.5%; loss on ignition 4.7%.
[0091] Step 2: Then, apply a surface glaze to the ceramic body obtained in Step 1 using a spray glazing method, followed by drying (hot air drying temperature 150 ℃, drying time 5 min). The chemical composition of the surface glaze includes, by mass percentage: SiO2 53.5%; Al2O3 27.5%; Fe2O3 0.3%; CaO 0.9%; MgO 0.3%; K2O 3.8%; Na2O 2.6%; ZrO2 6.3%; loss on ignition 4.8%. The specific gravity of the surface glaze is controlled at 1.40 g / cm³. 3 Glazing amount is 650 g / m 2 .
[0092] Step 3: Weigh out 15 parts by mass of potassium feldspar, 5 parts by mass of kaolin, 5 parts by mass of calcined zinc oxide, 5 parts by mass of calcium-zinc frit (its chemical composition is: by mass percentage, SiO2 55.6%; Al2O3 12.4%; ZnO 8.3%; ZrO2 0.1%; Fe2O3 0.1%; CaO 9.7%; MgO 1.2%; K2O 5.0%; Na2O 2.4%; BaO 4.6%; loss on ignition 0.6%), 10 parts by mass of zirconium silicate (artificially synthesized ZrSiO4, internal irradiation index 6.8, external irradiation index 4.5), and 15 parts by mass of yttrium-stabilized zirconium oxide (3YSZ, its chemical composition includes: by mass percentage, Y2O3 5.5%, ZrO2 94.5%; D... 50 10 parts by mass of high boron frit (its chemical composition includes, by mass percentage: SiO2 36.8%; Al2O3 10.0%; Fe2O3 0.3%; TiO2 0.1%; CaO 0.2%; MgO 0.1%; K2O 5.0%; Na2O 16.7%; B2O3 30.0%; loss on ignition 0.8%), and 35 parts by mass of alumina (purity 99.5%, D... 50 A glaze slurry was prepared by ball milling 0.5 parts by weight of water glass, 55 parts by weight of water, and 200 parts by weight of high-alumina grinding balls (5 μm in diameter) in a ball mill jar. The slurry residue was then controlled to be 0.3 wt% (325 mesh) by adjusting the ball milling time, and the specific gravity of the slurry was controlled to be 1.80 g / cm³ by adjusting the water content. 3 Thus, a radiation-cooled ceramic glaze can be prepared for use (its chemical composition includes, by mass percentage: SiO2 22.6%; Al2O3 40.9%; ZnO 5.4%; ZrO2 20.7%; Fe2O3 0.1%; CaO 0.5%; MgO 0.1%; K2O 2.3%; Na2O 2.3%; BaO 0.2%; B2O3 3.0%; Y2O3 0.8%; loss on ignition 1.1%).
[0093] Step 4: Apply a radiation-cooled ceramic glaze to the surface of the ceramic body obtained in Step 2 using a glazing method. The glaze application amount is 2000 g / m². 2 Then, it is dried (hot air drying temperature is 250 ℃, drying time is 10 min).
[0094] Step 5: The ceramic blank obtained in Step 4 is fired in a roller kiln at a temperature of 1160 ℃ for 45 min.
[0095] Step 6: After firing, the edges are ground, film is applied, and the bricks are packaged to obtain the radiation-cooled building ceramic bricks.
[0096] 70 mm × 150 mm ceramic samples were randomly cut using an external circular cutter. According to JG / T 235-2014 and T / CECS 10378-2024, the solar reflectance and atmospheric transparent window emissivity of the radiation-cooled building ceramic bricks were calculated to be 93% and 91%, respectively. The Vickers hardness of the radiation-cooled ceramic glaze was measured to be 8.3 GPa using Vickers indentation (0.5 kgf loading, held for 15 s). The stain resistance of the radiation-cooled ceramic bricks was only grade 3, as measured by GB / T 3810.14-2016. The difference between Comparative Example 3 and Example 1 is that the alumina content in the radiation-cooled ceramic glaze of Comparative Example 3 is as high as 35%, higher than the alumina content (30%) in Example 1; the corresponding zirconium silicate content decreased from 15% to 10%, resulting in an increase in Al2O3 content and a decrease in ZrO2 content in the formulation. Increasing the alumina content will not significantly degrade the radiative cooling performance of ceramics (the introduction of underfired pores will not reduce its solar reflectance, while the increase in Al2O3 content will increase the atmospheric transparency window emissivity of radiative cooling ceramics), but it will cause the ceramic glaze to be underfired, which will reduce its surface hardness and stain resistance.
[0097] Comparative Example 4 A method for preparing a radiation-cooled building ceramic brick mainly includes the following steps: Step 1: Prepare ceramic green bodies by dry pressing of ceramic green body powder, and then dry them (hot air drying temperature: 150 ℃, drying time: 5 min). The chemical composition of the ceramic green body includes, by mass percentage: SiO2 68.1%; Al2O3 18.4%; Fe2O3 1.2%; TiO2 0.2%; CaO 2.1%; MgO 1.0%; K2O 2.8%; Na2O 1.5%; loss on ignition 4.7%.
[0098] Step 2: Then, apply a surface glaze to the ceramic body obtained in Step 1 using a spray glazing method, followed by drying (hot air drying temperature 150 ℃, drying time 5 min). The chemical composition of the surface glaze includes, by mass percentage: SiO2 53.5%; Al2O3 27.5%; Fe2O3 0.3%; CaO 0.9%; MgO 0.3%; K2O 3.8%; Na2O 2.6%; ZrO2 6.3%; loss on ignition 4.8%. The specific gravity of the surface glaze is controlled at 1.50 g / cm³. 3 Glazing amount is 550 g / m 2 .
[0099] Step 3: Weigh out 5 parts by mass of potassium feldspar, 10 parts by mass of kaolin, 20 parts by mass of calcined zinc oxide, 13 parts by mass of calcium-zinc frit (its chemical composition includes, by mass percentage: SiO2 55.6%; Al2O3 12.4%; ZnO 8.3%; ZrO2 0.1%; Fe2O3 0.1%; CaO 9.7%; MgO 1.2%; K2O 5.0%; Na2O 2.4%; BaO 4.6%; loss on ignition 0.6%), 15 parts by mass of zirconium silicate (artificially synthesized ZrSiO4, internal irradiation index 6.8, external irradiation index 4.5), and 10 parts by mass of yttrium-stabilized zirconium oxide (3YSZ, its chemical composition includes, by mass percentage: Y2O3 5.5%, ZrO2 94.5%; D... 50 12 parts by mass of high boron frit (its chemical composition includes, by mass percentage: SiO2 36.8%; Al2O3 10.0%; Fe2O3 0.3%; TiO2 0.1%; CaO 0.2%; MgO 0.1%; K2O 5.0%; Na2O 16.7%; B2O3 30.0%; loss on ignition 0.8%) and 15 parts by mass of alumina (purity 99.5%, D... 50 The glaze slurry was prepared by ball milling with 1.0 part by weight of sodium humate (2 μm), 55 parts by weight of water, and 200 parts by weight of high-alumina grinding balls in a ball mill jar. The slurry residue was then controlled to be 0.3 wt% (325 mesh) by adjusting the ball milling time, and the specific gravity of the glaze slurry was controlled to be 1.90 g / cm³ by adjusting the water content. 3 Thus, a radiation-cooled ceramic glaze can be prepared for use (its chemical composition includes, by mass percentage: SiO2 24.9%; Al2O3 22.2%; ZnO 21.0%; ZrO2 19.2%; Fe2O3 0.2%; CaO 1.3%; MgO 0.2%; K2O 2.0%; Na2O 2.5%; BaO 0.6%; B2O3 3.6%; Y2O3 0.6%; loss on ignition 1.7%).
[0100] Step 4: Apply a radiation-cooled ceramic glaze to the surface of the ceramic body obtained in Step 2 using a glazing method. The glaze application amount is 1500 g / m². 2 Then, it is dried (hot air drying temperature is 200 ℃, drying time is 8 min).
[0101] Step 5: The ceramic blank obtained in Step 4 is fired in a roller kiln at a temperature of 1120 ℃ for 60 min.
[0102] Step 6: After firing, the edges are ground, film is applied, and the bricks are packaged to obtain the radiation-cooled building ceramic bricks.
[0103] 70 mm × 150 mm ceramic samples were randomly cut using an external cylindrical cutter. According to JG / T 235-2014 and T / CECS 10378-2024, the solar reflectance and atmospheric transparent window emissivity of the radiation-cooled building ceramic tiles were measured to be 90% and 91%, respectively. The stain resistance of the radiation-cooled ceramic tiles was determined to be level 4 using GB / T 3810.14-2016. Furthermore, the Vickers hardness of the radiation-cooled ceramic glaze was measured to be 8.5 GPa using Vickers indentation (0.5 kgf loading, held for 15 s). The difference between Comparative Example 4 and Example 3 is that the yttrium oxide-stabilized zirconium oxide content in Comparative Example 4 is only 10%, lower than the yttrium oxide-stabilized zirconium oxide content (35%) in Example 3. Correspondingly, the calcium-zinc frit content increases from 3% to 13%, the zirconium silicate content from 5% to 15%, and the alumina content from 10% to 15%. This leads to a decrease in the ZrO2 content in the ceramic glaze, while the SiO2 and Al2O3 contents increase. Since the decrease in ZrO2 content reduces the Mie scattering efficiency of the ceramic glaze, it significantly reduces the solar reflectance of the ceramic.
[0104] Comparative Example 5 A method for preparing a radiation-cooled building ceramic brick mainly includes the following steps: Step 1: Prepare ceramic green bodies by dry pressing of ceramic green body powder, and then dry them (hot air drying temperature: 150 ℃, drying time: 5 min). The chemical composition of the ceramic green body includes, by mass percentage: SiO2 68.1%; Al2O3 18.4%; Fe2O3 1.2%; TiO2 0.2%; CaO 2.1%; MgO 1.0%; K2O 2.8%; Na2O 1.5%; loss on ignition 4.7%.
[0105] Step 2: Then, apply a surface glaze to the ceramic body obtained in Step 1 using a spray glazing method, followed by drying (hot air drying temperature 150 ℃, drying time 5 min). The chemical composition of the surface glaze includes, by mass percentage: SiO2 53.5%; Al2O3 27.5%; Fe2O3 0.3%; CaO 0.9%; MgO 0.3%; K2O 3.8%; Na2O 2.6%; ZrO2 6.3%; loss on ignition 4.8%. The specific gravity of the surface glaze is controlled at 1.50 g / cm³. 3 Glazing amount is 550 g / m 2 .
[0106] Step 3: Weigh out 5 parts by mass of potassium feldspar, 5 parts by mass of kaolin, 20 parts by mass of calcined zinc oxide, 3 parts by mass of calcium-zinc frit (its chemical composition includes, by mass percentage: SiO2 55.6%; Al2O3 12.4%; ZnO 8.3%; ZrO2 0.1%; Fe2O3 0.1%; CaO 9.7%; MgO 1.2%; K2O 5.0%; Na2O 2.4%; BaO 4.6%; loss on ignition 0.6%), 5 parts by mass of zirconium silicate (artificially synthesized ZrSiO4, internal irradiance index 6.8, external irradiance index 4.5), and 40 parts by mass of yttrium-stabilized zirconium oxide (3YSZ, its chemical composition includes, by mass percentage: Y2O3 5.5%, ZrO2 94.5%; D... 50 12 parts by mass of high boron frit (its chemical composition includes, by mass percentage: SiO2 36.8%; Al2O3 10.0%; Fe2O3 0.3%; TiO2 0.1%; CaO 0.2%; MgO 0.1%; K2O 5.0%; Na2O 16.7%; B2O3 30.0%; loss on ignition 0.8%) and 10 parts by mass of alumina (purity 99.5%, D... 50 The glaze slurry was prepared by ball milling with 1.0 part by weight of sodium humate (2 μm), 55 parts by weight of water, and 200 parts by weight of high-alumina grinding balls in a ball mill jar. The slurry residue was then controlled to be 0.3 wt% (325 mesh) by adjusting the ball milling time, and the specific gravity of the glaze slurry was controlled to be 1.90 g / cm³ by adjusting the water content. 3 Thus, a radiation-cooled ceramic glaze can be prepared for use (its chemical composition includes, by mass percentage: SiO2 13.7%; Al2O3 14.1%; ZnO 20.1%; ZrO2 41.0%; Fe2O3 0.2%; CaO 0.3%; MgO 0.1%; K2O 1.4%; Na2O 2.3%; BaO 0.1%; B2O3 3.6%; Y2O3 2.2%; loss on ignition 0.9%).
[0107] Step 4: Apply a radiation-cooled ceramic glaze to the surface of the ceramic body obtained in Step 2 using a glazing method. The glaze application amount is 1500 g / m². 2 Then, it is dried (hot air drying temperature is 200 ℃, drying time is 8 min).
[0108] Step 5: The ceramic blank obtained in Step 4 is fired in a roller kiln at a temperature of 1120 ℃ for 60 min.
[0109] Step 6: After firing, the edges are ground, film is applied, and the bricks are packaged to obtain the radiation-cooled building ceramic bricks.
[0110] 40 mm × 40 mm ceramic samples were randomly cut using an external circular cutter. According to JG / T 235-2014 and T / CECS10378-2024, the solar reflectance and atmospheric transparent window emissivity of the radiation-cooled building ceramic bricks were measured to be 97% and 91%, respectively. Furthermore, the Vickers hardness of the radiation-cooled ceramic glaze was measured to be 8.9 GPa using Vickers indentation (0.5 kgf loading, held for 15 s). The difference between Comparative Example 5 and Example 3 is that the yttrium oxide-stabilized zirconium oxide content in Comparative Example 5 was 40%, higher than the zirconium oxide content (35%) in Example 3. The corresponding kaolin content decreased from 10% to 5%, which in turn increased the ZrO2 content in the ceramic glaze while decreasing the SiO2 and Al2O3 content. Increasing the ZrO2 content does not significantly degrade the solar reflectance, atmospheric transparency window emissivity, or surface hardness of the radiation-cooled ceramic, but it does increase the thermal expansion coefficient of the cooling glaze, causing the ceramic tile to warp. According to GB / T 3810.2-2016, its edge curvature was as high as -1.3 to +1.3%, exhibiting obvious warp deformation; while the edge curvature of the radiation-cooled ceramic tile prepared in Example 3 was only -0.5 to +0.5%.
[0111] Comparative Example 6 A method for preparing a radiation-cooled building ceramic brick mainly includes the following steps: Step 1: Prepare ceramic green bodies by dry pressing of ceramic green body powder, and then dry them (hot air drying temperature: 150 ℃, drying time: 5 min). The chemical composition of the ceramic green body includes, by mass percentage: SiO2 68.1%; Al2O3 18.4%; Fe2O3 1.2%; TiO2 0.2%; CaO 2.1%; MgO 1.0%; K2O 2.8%; Na2O 1.5%; loss on ignition 4.7%.
[0112] Step 2: Then, apply a surface glaze to the ceramic body obtained in Step 1 using a spray glazing method, followed by drying (hot air drying temperature 150 ℃, drying time 5 min). The chemical composition of the surface glaze includes, by mass percentage: SiO2 53.5%; Al2O3 27.5%; Fe2O3 0.3%; CaO 0.9%; MgO 0.3%; K2O 3.8%; Na2O 2.6%; ZrO2 6.3%; loss on ignition 4.8%. The specific gravity of the surface glaze is controlled at 1.40 g / cm³. 3 Glazing amount is 650 g / m 2 .
[0113] Step 3: Weigh out 15 parts by mass of potassium feldspar, 5 parts by mass of kaolin, 5 parts by mass of calcined zinc oxide, 5 parts by mass of calcium-zinc frit (its chemical composition is: by mass percentage, SiO2 55.6%; Al2O3 12.4%; ZnO 8.3%; ZrO2 0.1%; Fe2O3 0.1%; CaO 9.7%; MgO 1.2%; K2O 5.0%; Na2O 2.4%; BaO 4.6%; loss on ignition 0.6%), 15 parts by mass of zirconium silicate (artificially synthesized ZrSiO4, internal irradiation index 6.8, external irradiation index 4.5), and 15 parts by mass of yttrium-stabilized zirconium oxide (3YSZ, its chemical composition includes: by mass percentage, Y2O3 5.5%, ZrO2 94.5%; D... 50 10 parts by mass of high boron frit (its chemical composition includes, by mass percentage: SiO2 36.8%; Al2O3 10.0%; Fe2O3 0.3%; TiO2 0.1%; CaO 0.2%; MgO 0.1%; K2O 5.0%; Na2O 16.7%; B2O3 30.0%; loss on ignition 0.8%), and 30 parts by mass of alumina (purity 99.5%, D... 50 A glaze slurry was prepared by ball milling 0.5 parts by weight of water glass, 55 parts by weight of water, and 200 parts by weight of high-alumina grinding balls (5 μm in diameter) in a ball mill jar. The slurry residue was then controlled to be 0.3 wt% (325 mesh) by adjusting the ball milling time, and the specific gravity of the slurry was controlled to be 1.80 g / cm³ by adjusting the water content. 3 Thus, a radiation-cooled ceramic glaze can be prepared for use (its chemical composition includes, by mass percentage: SiO2 24.5%; Al2O3 35.8%; ZnO 5.4%; ZrO2 23.9%; Fe2O3 0.1%; CaO 0.5%; MgO 0.1%; K2O 2.3%; Na2O 2.3%; BaO 0.2%; B2O3 3.0%; Y2O3 0.8%; loss on ignition 1.1%).
[0114] Step 4: Apply a radiation-cooled ceramic glaze to the surface of the ceramic body obtained in Step 2 using a glazing method. The glaze application amount is 2200 g / m². 2 Then, it is dried (hot air drying temperature is 250 ℃, drying time is 10 min).
[0115] Step 5: The ceramic blank obtained in Step 4 is fired in a roller kiln at a temperature of 1160 ℃ for 45 min.
[0116] Step 6: After firing, the radiation-cooled building ceramic brick is obtained.
[0117] 40 mm × 40 mm ceramic samples were randomly cut using an external circular cutter. The solar reflectance and atmospheric transparent window emissivity of the radiation-cooled building ceramic bricks were measured to be 93% and 90%, respectively, using a UV-Vis-NIR spectrophotometer and a Fourier transform infrared spectrometer, respectively. The stain resistance of the radiation-cooled ceramic bricks was determined to be level 5 according to GB / T 3810.14-2016. The difference between Comparative Example 6 and Example 1 is that the specific gravity of the radiation-cooled ceramic glaze in Comparative Example 6 is 1.80 g / cm³. 3 Glazing amount is 2200 g / m 2 The specific gravity of the radiation-cooled ceramic glaze in Example 1 was 1.80 g / cm³. 3 Glazing amount is 2000 g / m 2 All other preparation process parameters were the same. Due to the increased application of the radiation-cooled ceramic glaze, the shape of the obtained radiation-cooled ceramic bricks deteriorated. According to GB / T 3810.2-2016, its edge curvature was as high as -1.5 ~ +1.5%, showing obvious warping deformation; while the edge curvature of the radiation-cooled ceramic bricks obtained in Example 1 was only -0.3 ~ +0.3%.
Claims
1. A radiation-cooled ceramic glaze, characterized in that, The chemical composition of the radiation-cooled ceramic glaze includes, by mass percentage: SiO2 16%~25%; Al2O3 15%~36%; ZnO 5%~21%; ZrO2 23%~37%; Fe2O3 0.1%~0.3%; TiO2 0%~0.1%; CaO 0.3%~1.5%; MgO 0.1%~0.2%; K2O 1.5%~2.3%; Na2O 2.2%~3.7%; BaO 0.1%~0.7%; B2O3 3%~6%; Y2O3 0.8%~2%; and loss on ignition 1%~2%.
2. The radiation-cooled ceramic glaze according to claim 1, characterized in that, The mineral composition of the radiation-cooled ceramic glaze includes: 5-15 parts potassium feldspar, 5-10 parts kaolin, 5-20 parts calcined zinc oxide, 3-15 parts calcium-zinc frit, 0-15 parts zirconium silicate, 15-35 parts yttrium-stabilized zirconium oxide, 10-20 parts high-boron frit, and 10-30 parts alumina, based on a total mineral composition of 100 parts by mass.
3. The radiation-cooled ceramic glaze according to claim 2, characterized in that, The chemical composition of the calcium-zinc ingot includes, by mass percentage: SiO2 50%~60%; Al2O3 10%~15%; ZnO 6%~11%; ZrO2 0~0.5%; Fe2O3 0~0.1%; TiO2 0~0.1%; CaO 8%~10%; MgO 1%~1.5%; K2O 3%~6%; Na2O 1%~3%; BaO 3%~5%; and loss on ignition 0~1%. The chemical composition of the high-boron ingot includes, by mass percentage: SiO2 32%~40%; Al2O3 5%~15%; Fe2O3 0~0.3%; TiO2 0~0.1%; CaO 0~0.2%; MgO 0~0.2%; K2O 4%~6%; Na2O 12%~20%; B2O3 25%~35%; and loss on ignition 0.5%~1.5%.
4. The radiation-cooled ceramic glaze according to any one of claims 1 to 3, characterized in that, The phase composition of the radiative cooling ceramic glaze after firing is mainly crystalline, with t-ZrO2, m-ZrO2, ZrSiO4, ZnAl2O4, and Al2O3 being the main crystalline phases.
5. Radiant cooling building ceramic bricks, characterized in that, The radiation-cooled building ceramic bricks include a radiation-cooled ceramic glaze layer formed using a radiation-cooled ceramic glaze according to any one of claims 1 to 4.
6. The radiant cooling building ceramic brick according to claim 5, characterized in that, Radiation-cooled ceramic tiles have a solar reflectance of ≥93% and an atmospheric transparency window emissivity of ≥90%.
7. A method for preparing radiant cooling building ceramic bricks, characterized in that, Includes the following steps: Step 1: Apply a surface glaze to the ceramic body and allow it to dry. Step 2: Apply a radiation-cooled ceramic glaze according to any one of claims 1 to 4 to the surface of the ceramic blank obtained in step 1 and then dry it again; Step 3: The ceramic blank obtained in step 2 is fired to produce radiation-cooled building ceramic bricks.
8. The preparation method according to claim 7, characterized in that, The radiation-cooled ceramic glaze is applied by glazing; the specific gravity of the radiation-cooled ceramic glaze is 1.80~1.95 g / cm³. 3 The glaze application rate is 1200~2000 g / m². 2 .
9. The preparation method according to claim 7, characterized in that, The chemical composition of the glaze includes, by mass percentage: SiO2 50%~58%; Al2O3 25%~30%; Fe2O3 0.2%~0.5%; TiO2 0%~0.2%; CaO 0.5%~1%; MgO 0.1%~0.5%; K2O 2%~5%; Na2O 2%~3.5%; ZrO2 4%~8%; and loss on ignition 3%~6%.
10. The preparation method according to claim 7, characterized in that, The glaze is applied by pouring or spraying; the specific gravity of the glaze is 1.40~1.55 g / cm³. 3 The glaze application rate is 450~650 g / m². 2 .
11. The preparation method according to claim 7, characterized in that, The firing temperature is 1120~1160 ℃, and the firing time is 30~60 min.
Citation Information
Patent Citations
Passive radiation refrigeration ceramic and preparation method thereof
CN117534506A
Ceramic tile with radiation refrigeration function as well as preparation method and application of ceramic tile
CN117756409A
Radiation refrigeration glaze, preparation method thereof and lightweight ceramic tile
CN119591321A
Radiation refrigeration ceramic tile as well as preparation method and application thereof
CN121362029A
Radiation refrigeration ceramic tile and preparation method thereof
CN122102516A